Augmented the Structure, Electronic and Optical Characteristics of PEO Doped NiO for Electronics Applications - Hassan, Huda Bukheet; Abduljalil, Hayder M.; Hashim, Ahmed (Physics and Chemistry of Solid State, 2021)
This paper aims to investigate the structural, optical and electrical properties of PEO doped with NiO. The DFT calculations have been performed using Gaussian 09 package of programs. The calculated electronic properties included the total energy, HOMO and LUMO energies, energy gap, ionization energy, electron affinity, electronegativity, electrochemical hardness, electronic softness and electrophilic index. The obtained results showed that the doping PEO with NiO improved the structural, optical, electronic and electrical characteristics where the energy band gap decreases about 67.4% with addition of NiO which make the (PEO-NiO) composites are promising materials for flexible optoelectronics fields in the development of electronics applications.